Efficacy of sedomil 72WP and recozeb 80WP to control die back (Colletotrichum gloeosporioides) of tea in Bangladesh (The Journal of Plant Protection Sciences, 2023)
A study was conducted to find out the efficacy of sedomil 72WP (mancozeb) and recozeb 80WP (mancozeb +  metalaxyl) to control of dieback disease (Colletotrichum gloeosporioides) of tea in Bangladesh. The pathogen, C.  gloeosporioides was isolated from the dieback infected tea twigs on PDA medium. Mycelial blocks of the isolated  pathogen were transferred to PDA plates amended with sedomil 72WP (mancozeb) @ 720, 1080, 1440 and 1800  ppm and recozeb 80WP (mancozeb + metalaxyl) @ 800, 1200, 1600 and 2000 ppm concentrations. Sedomil 72WP  and recozeb 80WP caused colony growth inhibition, respectively by 75.00-90.77% and 75.88-91.33% in 2008 and  74.66-90.55% and 75.66-91.11% in 2009. In a field experiment at the main farm of Bangladesh Tea Research In stitute (BTRI), both fungicides were applied as foliar spray for three times at 1.0, 1.5, 2.0 and 2.5 kg ha-1. In 2008,  sedomil 72WP gave 45.52-92.78% and recozeb 80WP gave 46.47- 90.39% reduction in PDI. In 2009, the reduc tion in PDI was 45.84-90.83% and 45.65-89.98% respectively under sedomil 72WP and recozeb 80WP. The use of  sedomil 72WP and recozeb 80WP @ 2.5 kg ha-1and 2.0 kg ha-1are equally effective in controlling the disease.  Both the fungicides are recommended at 2.0 kg ha-1against the dieback disease of tea and its causal organism.
Keywords: Tea; dieback diseases; Colletotrichum gloeosporioides; mancozeb